Work-rich and work-poor. Three decades of change - Joseph Rowntree Foundation, York; Berthoud, Richard (Bristol, 2007)
"An analysis of trends in the distribution of jobs between social groups, this report tracks the number of non-working families in Britain over the last three decades.